A prospective study on the epidemiology and clinical significance of viral respiratory infections among pediatric oncology patients. (3rd April 2019) - Vliora, Christianna; Papadakis, Vassilios; Doganis, Dimitrios; Tourkantoni, Natalia; Paisiou, Anna; Kottaridi, Christine; Kourlamba, Georgia; Zaoutis, Theoklis; Kosmidis, Helen; Kattamis, Antonis; Polychronopoulou, Sophia; Goussetis, Evgenios; et al.
Abstract: Respiratory infections in oncology are both common and potentially severe. However, there is still a gap in the literature, regarding the epidemiology of viral respiratory infections in children with cancer. We prospectively enrolled 224 patients, from September 2012 to August 2015. The cohort included children with hematologic or solid malignancies receiving chemotherapy, or undergoing hemopoietic stem cell transplantation, outpatients/inpatients exhibiting signs/symptoms of febrile/afebrile upper/lower respiratory infection. Viral infection was diagnosed by detection of ≥1 viruses from a sample at time of enrollment, using the CLART ® PneumoVir kit (GENOMICA, Spain). Α detailed questionnaire including demographics and medical history was also completed. Samples were processed in batches, results were communicated as soon as they became available. Children recruited in whom no virus was detected composed the no virus detected group. Viral prevalence was 38.4% in children presenting with respiratory illness. A single virus was found in 30.4%, with RSV being the most frequent. Viral coinfections were detected in 8%. Children with viral infection were more likely to be febrile upon enrollment and to present with lower respiratory signs/symptoms. They had longer duration of illness and they were more likely to receive antibiotics/antifungals. Only 22% of children with influenza received oseltamivir. Mortality was low (2.7%), however, pediatric intensive care unit (PICU) admission and death were correlated with virus detection. In our study mortality was low and PICU admission was related to virus identification. Further research is needed to clarify whether antibiotics in virus-proven infection are of value and underline the importance of oseltamivir's timely administration in influenza.